Anaerobic solid-state fermentation with Bacillus subtilis for digesting free gossypol and improving nutritional quality in cottonseed meal - Li, Jia; Gao, Tongguo; Hao, Zhimin; Guo, Xiaojun; Zhu, Baocheng (Frontiers in Nutrition, 2022)
This study evaluated the effects of fermentation with Bacillus sp. on gossypol degradation and nutritional quality improvement in cottonseed meal (CM), as well as the changes of bacterial community structure during fermentation. The strains with high activity for digesting free gossypol were screened from high protease-producing strains preserved in the laboratory. Then the strains which had both the gossypol degradation activity and protease producing activity were selected to degrade macromolecular protein and free gossypol in CM. The unsterilized SSF medium was inoculated with 109 CFU/kg Bacillus culture and fermented at room temperature for 14 days. Each group had three parallels. And the effects of anaerobic solid-state fermentation on unsterilized CM was evaluated. Results showed that for the seven strains with high activity for digesting free gossypol and producing protease that were screened, free gossypol content in fermented cottonseed meal (FCM) decreased and acid-soluble protein (ASP) contents increased. Among them, strain M-15 had the best fermentation effect, with the free gossypol degradation rate of 93.46% and acid soluble protein content of 13.26%. M-15 was identified as Bacillus subtilis. During fermentation with M-15, the bacterial diversity in CM was reduced, but not significant and the community structure was simpler significantly. The strain M-15 selected in this experiment reduced the free gossypol content and improved the nutritional quality of CM through anaerobic solid-state fermentation, which can be used for industrial large-scale production.